Inovasi Dialogis: Menuju Transformasi Pelayanan Publik Yang Partisipatif (Kajian Sistem Pelayanan Malang Online) - Krishno Hadi; Listiana Asworo; Iradhad Taqwa (Journal of Government and Civil Society, 2020)
This article highlights the importance of a dialogic relationship between government and society in the effort to build more participatory service system innovations. The idea of dialogic innovation itself arises as a logical consequence of the open government system, which replaces outdated service practices. This new idea emphasizes accountability, transparency and participation from the community as the spirit of the public service system. Thus, public service innovation is produced by absorbing bottom-up innovation. This research uses a qualitative approach with a case study model. Data collected through observation, depth interviews and documentation. The results of this study indicate that the Malang Online Service System (SINGO) implemented in the village of Sawojajar, Malang is evidence of the success of dialogic innovation between the community and the government. The android application-based public service system was conceived and created by the Sawojajar community itself, supported by the local government. SINGO’s innovations have succeeded in becoming champions and pioneers for other villages. This shows that dialogical and participatory public services have succeeded in changing the old pathological bureaucratic paradigm into emancipation. Artikel ini menyoroti pentingnya relasi dialogis antara pemerintah dengan masyarakat dalam upaya membangun inovasi sistem layanan yang lebih partisipatif. Gagasan inovasi dialogis sendiri muncul sebagai konsekuensi logis dari sistem open government, yang menggantikan praktik pelayanan yang telah usang. Ide baru ini menitikberatkan pada akuntabilitas, transparansi serta partisipasi dari masyarakat sebagai ruh dari sistem pelayanan publik. Sehingga, inovasi pelayanan publik dihasilkan dengan cara menyerap aspirasi dari bawah (bottom-up innovation). Penelitian ini menggunakan pendekatan kualitatif dengan model studi kasus. Data dikumpulkan melalui observasi, depth interview dan dokumentasi. Hasil penelitian ini menunjukan bahwa Sistem Pelayanan Malang Online (SINGO) yang diterapkan di kelurahan Sawojajar, Malang merupakan bukti dari keberhasilan inovasi dialogis antara masyarakat dengan pemerintah. Sistem pelayanan publik berbasis aplikasi android digagas dan diciptakan oleh masyarakat Sawojajar sendiri, didukung oleh pemerintah setempat. Inovasi SINGO sendiri berhasil menjadi juara sekaligus pionir bagi kelurahan lainnya. Hal ini menunjukkan bahwa pelayanan publik yang dialogis dan partisipatif berhasil mengubah paradigma birokrasi lama yang patologis menjadi emansipatif.